2017
DOI: 10.1111/jrh.12268
|View full text |Cite
|
Sign up to set email alerts
|

Polysubstance Use Among Adolescents in a Low Income, Rural Community: Latent Classes for Middle‐ and High‐School Students

Abstract: In general, younger adolescents have lower overall use rates, but within certain classes identified by this analysis, the observed pattern suggests that younger cohorts are turning to prescription drugs and inhalants. These findings support the implementation of universal substance use prevention programs, targeted programs for youth experiencing risk factors associated with substance use, and improved rural substance abuse treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…As the rst study to ascertain sub-phenotypes of risk pro les among Canadian youth, our research sheds light on risk pro ling with cross-sectional and longitudinal evidence. Our ndings are consistent with previous studies that employ statistical modelling approaches in determining risk factors 16,17,18,19,31,36,38 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As the rst study to ascertain sub-phenotypes of risk pro les among Canadian youth, our research sheds light on risk pro ling with cross-sectional and longitudinal evidence. Our ndings are consistent with previous studies that employ statistical modelling approaches in determining risk factors 16,17,18,19,31,36,38 .…”
Section: Discussionsupporting
confidence: 93%
“…The insights gained from exploring the risk factors linked to substance use in mid-adolescence can be leveraged to create tailored prevention and intervention strategies aimed at reducing substance use among young individuals. Age, sex, and ethnicity are well-established individual-level risk factors that impact adolescent substance use 16,17,18,19,20,21,22 , but other factors such as depression and sedentary behavior also play a signi cant role 22,23,24 . Additionally, eating habits, social connectedness, family and peer in uence 25,26 , and low social connectedness 27 may in uence the risk of youth substance use.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining studies used data from European countries (n=12), South America (n=1) and Australasia (n=3). 37 studies were based on general population samples; two studies used socioeconomically deprived samples [21,22] and two further studies focused on specific ethnic minorities, namely Latino adolescents [23] and a comparison of 'White American', 'American Indian' and 'Alaskan natives' [24]. Sample sizes varied substantially from 234 to 46,283 (M=7754.73, SD=9050.72).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Twenty-three studies employed latent class analysis, ten undertook cluster analysis, seven used factor analysis, and one used principal component and factor analysis. Three studies reported separate groups for gender [18,25,26], two for age [19,22] and one for ethnicity [27]. Due to this limited sample, no comparisons between sub-groups are undertaken here, the limitations of this are outlined in the discussion.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation